Influence of Acute High-Intensity Aerobic Interval Exercise Bout on Selective Attention and Short-Term Memory Tasks. Issue 1 (February 2014) - Alves, Christiano R. R.; Tessaro, Victor H.; Teixeira, Luis A. C.; Murakava, Karina; Roschel, Hamilton; Gualano, Bruno; Takito, Monica Y.
Acute moderate intensity continuous aerobic exercise can improve specific cognitive functions, such as short-term memory and selective attention. Moreover, high-intensity interval training (HIT) has been recently proposed as a time-efficient alternative to traditional cardiorespiratory exercise. However, considering previous speculations that the exercise intensity affects cognition in a U-shaped fashion, it was hypothesized that a HIT session may impair cognitive performance. Therefore, this study assessed the effects of an acute HIT session on selective attention and short-term memory tasks. 22 healthy middle-aged individuals ( M age = 53.7 yr.) engaged in both (1) a HIT session, 10 1 min. cycling bouts at the intensity corresponding to 80% of the reserve heart rate interspersed by 1 min. active pauses cycling at 60% of the reserve heart rate and (2) a control session, consisting of an active condition with low-intensity active stretching exercise. Before and after each experimental session, cognitive performance was assessed by the Victoria Version of the Stroop test (a selective attention test) and the Digit Span test (a short-term memory test). Following the HIT session, the time to complete the Stroop "Color word" test was significantly lower when compared with that of the control session. The performances in the other subtasks of the Stroop test as well as in the Digit Span test were not significantly different. A HIT session can improve cognitive function.